Soft Skills Representation in English and Russian Songs - M. V. Petrova; S. V. Pristupa; G. A. Rozhkov; A. P. Tumanova (Дискурс)
Introduction. This paper is aimed at analyzing the songs of the British group “The Beatles”, and the songs of the Russian artist, poet and singer V. Vysotsky for the purpose of their soft skills representation. The relevance of the work is determined by the general, keen interest to the formation and development of social competences as the foundation of improving successful interpersonal relations in the 21st century. The novelty of the research lies in the fact that for the first time the study of soft skills was carried out on the basis of the creative work of the prominent representatives of the Russian and British musical culture of the past century.Methodology and sources. Due to the fact that the musical creativity of "The Beatles" and V. Vysotsky was considered primarily from the standpoint of linguistic material, the research methodology was based on the principles of linguistic text analysis, such as methods of component, cognitive and discourse analysis. In addition, the paper analyzes the works of domestic and foreign scientists devoted to the basic principles of the formation and development of soft skills of a person today.Results and discussion. The article demonstrates a new, non-standard approach when working with the mastery and training of soft skills. The development of creative abilities directly depends on the emotional response that the material evokes. Music compositions have a more intense impact on a person, because they combine two components: lyrics and tune. Therefore, the analysis of songs can serve as an additional source of improving creative thinking. Comparison of soft skills representation in Russian and English songs did not reveal any clear distinctive national features of the skills under consideration, which once again proves their universality.Conclusion. The study of artistic images and metaphors presented in the lyrics of both Russian and English singers can form the basis of a new methodological approach aimed at developing non-standard, creative thinking, which can be applied at various levels of the educational process.